2020
DOI: 10.1002/sys.21550
|View full text |Cite
|
Sign up to set email alerts
|

Assaying the importance of system complexity for the systems engineering community

Abstract: How should organizations approach the evaluation of system complexity at the early stages of system design in order to inform decision making? Since system complexity can be understood and approached in several different ways, such evaluation is challenging. In this study, we define the term “system complexity factors” to refer to a range of different aspects of system complexity that may contribute differentially to systems engineering outcomes. Views on the absolute and relative importance of these factors f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…A previous study collected judgments from current systems engineering practitioners on the relative and absolute importance of several different system complexity factors identified that additional relevant system complexity factors could include consideration of the number and diversity of system interfaces and dependencies, nonfunctional requirements, and “client/customer/user complexity (e.g., their understanding of the system, novelty of the system to them, willingness to accept change).” 86 For the Thales Group “Complexity Profiler,” this finding implicates that the complexity factors encoded in the tool requires updating, preferably via a combination of literature survey and a survey of experienced systems engineering managers from across the organization. However, care must be taken with the addition of more system complexity factors to such tools to ensure that the factors are adequately and unambiguously defined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study collected judgments from current systems engineering practitioners on the relative and absolute importance of several different system complexity factors identified that additional relevant system complexity factors could include consideration of the number and diversity of system interfaces and dependencies, nonfunctional requirements, and “client/customer/user complexity (e.g., their understanding of the system, novelty of the system to them, willingness to accept change).” 86 For the Thales Group “Complexity Profiler,” this finding implicates that the complexity factors encoded in the tool requires updating, preferably via a combination of literature survey and a survey of experienced systems engineering managers from across the organization. However, care must be taken with the addition of more system complexity factors to such tools to ensure that the factors are adequately and unambiguously defined.…”
Section: Resultsmentioning
confidence: 99%
“…The lack of a consensus view within the systems engineering community on the relative importance of different system complexity factors causes an additional challenge. That systems engineers are not aligned with each other on how important system complexity factors are, and may not appreciate the extent or nature of these misalignments, may hinder efforts to effectively identify, evaluate, and manage sources of system complexity 86 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, organizations that recognize these distinctions realize a better understanding of the interplay of scientific and heuristic pathways driving the emergence and evolution of system principles and methods across science and engineering fields 26 . We assert there are benefits, both practical and philosophical, for organizations to embrace an integrated project complexity narrative that addresses the challenges associated with contested definitions of systems complexity 15,68 and project complexity 5,54 …”
Section: Discussionmentioning
confidence: 99%
“…This aligns with the three types of structural complexity described by Sheard and Mostashari 17 that is, size, architecture and connectivity. It is also the type of complexity that has seen the most extensive development of complexity metrics 16,68,69 and the concept with the most mentions in both project and system complexity literature. Structural complexity should be understood as applicable to both engineered systems and the organizations put in place to deliver them.…”
Section: Introductionmentioning
confidence: 99%